FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN OBESITAS PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS KRISTEN INDONESIA - Diani, Yusias HIkmat (Jurnal Ilmiah Widya, 2018)
Obesity has become a major concern in the world, especially in young adults students in college. The students are more vulnerable and have the highest risk of obesity compared to the general population. This study aims to determine the relationship of sex, father's nutritional status, maternal nutritional status, residence status, diet, sleep duration and physical activity to obesity in 2013 students of the Faculty of Medicine, Christian University of Indonesia in East Jakarta in June - July 2016. The method the research used was cross sectional with sample in this study was the 2013 FKUKI class of 215 students out of 260 total population. The data collected by questionnaires and anthropometric data obtained from measurements of body weight and height to determine the Body Mass Index (BMI). The statistical test used is chi square and logistic regression test. The result of the research showed that: The proportion of obese students in this study was obtained at 35.5%. Variables that are significantly related to obesity in students are gender, maternal nutritional status, physical activity and father's nutritional status. Variables that are not related to obesity in students are diet, sleep duration and residence status.